Matisse - Selz, Jean. 4 0 16; 5 (New York : Crown Publishers, 1990)
Text and reproductions of paintings and drawings present a critical analysis of the artist and his work.
Translation of: Matisse.
Includes bibliographical references (p.94-95) and index.
Young Adult;Young Adult
Keywords: Matisse, Henri,;Matisse, Henri, -- Criticism and interpretation.0 -- 1869-1954;1869-1954.; 6; Painters -- France; 20; 2